To simplify the expression, we can apply the properties of integer exponents.
First, let's start by rearranging the expression to have only positive exponents using the negative exponent property:
(4^3 * 7^-2)^-5 / 7^9 * 4^-13
= (4^3)^-5 * (7^-2)^-5 / 7^9 * 4^-13
Now, let's simplify each term separately:
(4^3)^-5 = 4^(3 * -5) = 4^-15
(7^-2)^-5 = 7^(-2 * -5) = 7^10
4^-13 = 1/4^13 = 1/4^13
Substituting these simplified terms back into the expression, we have:
(4^3 * 7^-2)^-5 / 7^9 * 4^-13
= 4^-15 * 7^10 / 7^9 * 1/4^13
Next, let's simplify the terms with the same base:
4^-15 * 7^10 / 7^9 * 1/4^13
= 7^(10-9) * 4^(-15-13)
= 7^1 * 4^-28
= 7/4^28
Therefore, the simplified fraction is 7/4^28.
Apply the Properties of Integer Exponents to generate equivalent expressions with only positive exponents, then solve the expression. Your answer will be a simplified fraction with no remaining exponents. (4^3 * 7^-2)^-5/ 7^9 * 4^-13
3 answers
no :(
what is th answer